2021
DOI: 10.1177/20543581211032857
|View full text |Cite
|
Sign up to set email alerts
|

Voicing Individual Concerns for Engagement in Hemodialysis (VOICE-HD): A Mixed Method, Randomized Pilot Trial of Digital Health in Dialysis Care Delivery

Abstract: Background: People receiving in-center hemodialysis (HD) have prioritized the need for more individualized health information and better communication with nephrologists. The most common setting for patient-nephrologist interactions is during the HD treatment, which is a time pressured setting that lacks privacy. Objective: To facilitate effective communication in the hemodialysis (HD) unit, we evaluated the usability of a web application (web app) from both the patient and physician perspective. The main aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 20 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…38 In this study, despite demonstrated patient acceptance and utility of the app, nephrologists felt that the tool interrupted workflow, which was a barrier to adoption into clinical care. 38 Only 20% of patient participants used web-based technology prior to the study, thus emphasizing the need for technological literacy training and the possibility that such solutions may not be relevant to all persons receiving hemodialysis. [38][39][40] Limitations of this study include that all participants were English-speaking and from urban in-center hemodialysis units in Canada.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…38 In this study, despite demonstrated patient acceptance and utility of the app, nephrologists felt that the tool interrupted workflow, which was a barrier to adoption into clinical care. 38 Only 20% of patient participants used web-based technology prior to the study, thus emphasizing the need for technological literacy training and the possibility that such solutions may not be relevant to all persons receiving hemodialysis. [38][39][40] Limitations of this study include that all participants were English-speaking and from urban in-center hemodialysis units in Canada.…”
Section: Discussionmentioning
confidence: 80%
“…38 In this study, despite demonstrated patient acceptance and utility of the app, nephrologists felt that the tool interrupted workflow, which was a barrier to adoption into clinical care. 38 Only 20% of patient participants used web-based technology prior to the study, thus emphasizing the need for technological literacy training and the possibility that such solutions may not be relevant to all persons receiving hemodialysis. 38-40…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations